Enantioselectivity in the boron aldol reactions of methyl ketones. - Goodman, J; Paton, R (Royal Society of Chemistry, 2007)
DFT computed transition states quantitatively explain the surprising stereochemical outcome of unsubstituted enolborinates in diastereoselective and enantioselective boron aldol reactions.